Experimental infection of chicken embryos with recently described Brucella microti: Pathogenicity and pathological findings. (August 2015) - Wareth, Gamal; Böttcher, Denny; Melzer, Falk; Shehata, Awad Ali; Roesler, Uwe; Neubauer, Heinrich; Schoon, Heinz-Adolf
Graphical abstract: Highlights: We study the virulence of Brucella microti in chicken embryos. B. microti is able to infect and to replicate in chicken embryos very efficiently. Chicken embryos are a useful model to study the pathogenesis of brucellosis. Inoculation of embryonated eggs seems to be a useful tool to isolate B. microti. Abstract: Brucellae are facultative intracellular pathogens causing disease in a wide range of domestic and wild animals as well as in humans. Brucella (B.) microti is a recently recognized species and was isolated from common voles ( Microtus arvalis ), red foxes and soil in Austria and the Czech Republic. Its pathogenicity for livestock and its zoonotic potential has not been confirmed yet. In the present study 25 SPF chicken embryos were inoculated at day 11 of age with 1.6 × 10 3 and 1.6 × 10 5 B. microti by yolk sac and allantoic sac routes. Re-isolation of B. microti indicated rapid multiplication of bacteria (up to 1.7 × 10 12 CFU). B. microti provoked marked gross lesions, i.e. hemorrhages and necroses. All inoculated embryos were dead (100% mortality) in between 2nd and 4th day post inoculation. The predominant histopathological lesion was necroses in liver, kidneys, lungs, spleen, gastrointestinal tract, spinal meninges, yolk sac and chorioallantoic membrane. Immunohistochemical examination showed the presence of Brucella antigen in nearly all of these organs, with infection being mainly restricted to non-epithelial cells or tissues. This study provides the first results on the multiplication and pathogenicity of the mouse pathogenic B. microti in chicken embryos. These data suggest that, even though chicken are not mammals, they could provide a useful tool for understanding the pathogenesis of B. microti associated disease.